Tension-Free Vaginal Tape Failure After Robotic Sacrocolpopexy and Tension-Free Vaginal Tape for Concomitant Prolapse and Stress Incontinence. Issue 5 (September 2015) - Osmundsen, Blake; Gregory, W. Thomas; Denman, Mary Anna; Adams, Kerrie; Edwards, Renee; Clark, Amanda
Abstract : Objective: Evidence of surgical cure with tension free vaginal tape (TVT) is robust for isolated stress urinary incontinence, but rigorous studies investigating combined prolapse and incontinence are lacking. Our study measured cure of stress incontinence in concomitant robotic sacrocolpopexy and retropubic sling (TVT). We hypothesized a higher rate of objective failure as measured by the cough stress test (CST) compared to failures reported in recent randomized trials of TVT in patients without prolapse (aggregate 8% failure). Methods: Prospective cohort of patients with stress incontinence and prolapse, scheduled for robotic sacrocolpopexy and TVT. Outcomes assessed at 12 months: CST (primary aim), Patient Global Impression of Improvement (PGI-I), Pelvic Floor Distress Inventory, and the Sandvik questionnaire. Results: Sixty-six of 77 subjects (86%) completed follow-up. Average age was 65 years, 96% were white, with mean body mass index of 28.1 kg/m 2 . Mean parity was 2.7, 50% had a previous hysterectomy. Mean leading edge of prolapse was +2.3 cm. All patients underwent the planned surgery; additionally, 50% underwent hysterectomy and 38% posterior colporrhaphy. The TVT failure (+CST) was 19.7% (95% confidence interval, 11.3%–31.7%; P < 0.001 compared to 8%). Neither preoperative disease severity, nor preoperative prolapse stage affected risk of failure of TVT. Eighty-three percent of the subjects were happy or very happy (PGI-I). However, those with a positive CST (failure) had significantly less satisfaction on PGI-I, UDI-6, and Pelvic Floor Distress Inventory-20. Conclusions: In this population with advanced prolapse, cure of stress urinary incontinence by TVT in setting of robotic sacrocolpopexy is lower compared to published trials where prolapse is absent. Women are less satisfied when the postoperative CST is positive. Abstract : The TVT sling fails to cure stress incontinence in 20% of women when performed with a robotic sacrocolpopexy for pelvic organ prolapse.